Analyzing The Effect Of Transformational Leadership On Organizational Effectiveness: Evidence From Ramayana - Vishal Gupta; Ashish Ranjan Sinha (International Journal of Psychosocial Rehabilitation, 2020)
Transformational leadership is one of the most important and essential leadership styles that encourages and inspires employees to innovate and develop new ways to grow and improve the path to organizational future success. An organization needs a leader who can lead the entire team and move them to achieve the organizational goal. But this is the old philosophy. Today we need a leader who can create more leaders than followers. A real leader is someone who not only wants to lead the team or create followers but rather he would like to create or transform more leaders. In this research paper, attempts have been made to analyze the effect of transformational leadership traits possessed by all-time great lord Rama and its impact on leadership qualities developed in Bharat, Angad, Sugriva etc. who are important characters of Ramayana epic. By analysing and following the transformational leadership style, organizational effectiveness can be achieved.